PERFORMANCE CONTROL’S EFFECT ON SMKN 3 PEKANBARU’S WORK DISCIPLE AND TEACHER PERFORMANCE - Elfiya Yetti; Sopiah Sopiah (Indonesian Journal of Multidisciplinary Science, 2022)
This study aims to analyze the effect of work supervision on work discipline and teacher performance at SMK Negeri 3 Pekanbaru. Meanwhile, the research was carried out from April to June 2020. The data source for this research was the teachers of SMK Negeri 3 Pekanbaru with 51 respondents as the research sample. The data collection technique used the census method. In addition, the data analysis technique was descriptive analysis, validity and reliability tests, normality and linearity tests, and hypothesis testing, namely path analysis tests. The results of the study: Sub Structure 1 shows direct work supervision (X) has a significant positive effect on work discipline (Y 1) with an influence value of 35.9%. Sub Structure 2 shows that work supervision (X) and work discipline (Y1) has a significant positive effect on teacher performance (Y2) at SMK Negeri 3 Pekanbaru, with an influence value of 79%. Furthermore, the indirect effect shows; Work supervision (X) has a significant positive effect on teacher performance (Y2) through work discipline (Y1) teachers at SMK Negeri 3 Pekanbaru